The effects of aeration and irrigation regimes on soil CO2 and N2O emissions in a greenhouse tomato production system - Hui CHEN; Hui-jing HOU; Xiao-yun WANG; Yan ZHU; Qaisar Saddique; Yun-fei WANG; Huanjie CAI (Journal of Integrative Agriculture, 2018)
Aerated irrigation has been proven to increase crop production and quality, but studies on its environmental impacts are sparse. The effects of aeration and irrigation regimes on soil CO2 and N2O emissions in two consecutive greenhouse tomato rotation cycles in Northwest China were studied via the static closed chamber and gas chromatography technique. Four treatments, aerated deficit irrigation (AI1), non-aerated deficit irrigation (CK1), aerated full irrigation (AI2) and non-aerated full irrigation (CK2), were performed. The results showed that the tomato yield under aeration of each irrigation regime increased by 18.8% on average compared to non-aeration, and the difference was significant under full irrigation (P<0.05). Full irrigation significantly increased the tomato yield by 23.9% on average in comparison to deficit irrigation. Moreover, aeration increased the cumulative CO2 emissions compared to non-aeration, and treatment effects were significant in the autumn-winter season (P<0.05). A slight increase of CO2 emissions in the two seasons was observed under full irrigation (P>0.05). There was no significant difference between aeration and non-aeration in soil N2O emissions in the spring-summer season, whereas aeration enhanced N2O emissions significantly in the autumn-winter season. Furthermore, full irrigation over the two seasons greatly increased soil N2O emissions compared to the deficit irrigation treatment (P<0.05). Correlation analysis indicated that soil temperature was the primary factor influencing CO2 fluxes. Soil temperature, soil moisture and NO3− were the primary factors influencing N2O fluxes. Irrigation coupled with particular soil aeration practices may allow for a balance between crop production yield and greenhouse gas mitigation in greenhouse vegetable fields.